The relationship of job and life satisfaction with symptoms of anxiety, depression, and irritability/anger in nurses - Serzysko, Bogusława; Mroczkowska, Renata; Kamińska, Jolanta; Podsiadło, Beata; Żarczyński, Grzegorz; Krajza, Anna (Frontiers in Public Health, 2025)
IntroductionThe nursing profession involves substantial emotional and organizational demands, which may negatively affect nurses’ mental health and overall satisfaction with life and work.ObjectiveTo assess the levels of anxiety, depression, and irritability/anger symptoms in nurses and examine their associations with life and job satisfaction. In this study, the HADS-M subscale assessing irritability/anger was used. It captures symptoms of irritability and anger but does not measure aggression or anger expression as behavioral constructs.MethodsA cross-sectional online survey was conducted among 538 registered nurses in Poland. Validated instruments were applied: HADS-M (for anxiety, depression, and irritability/anger symptoms), SWLS (life satisfaction), and SSP (job satisfaction). Statistical analyses included descriptive statistics, Spearman’s rank-order correlations, internal consistency (Cronbach’s alpha), and multiple linear regression (two-tailed, α = 0.05).ResultsA high prevalence of psychological symptoms was observed. All symptom domains were significantly and negatively correlated with life and job satisfaction (p < 0.001). Multiple regression analyses indicated that depressive symptoms were the strongest predictors of both life satisfaction (β = −0.429) and job satisfaction (β = −0.315), followed by irritability/anger symptoms. All models were statistically significant (p < 0.001).ConclusionAnxiety, depression, and irritability/irritability/anger symptoms significantly reduce nurses’ satisfaction with life and work. Depressive symptoms exerted the most profound impact. These findings emphasize the urgent need for targeted mental health support programs and preventive strategies to enhance nurses’ well-being and professional performance.